Pengaruh Literasi Keuangan dan Kemudahan Belanja Online tehradap Pengelolaan Keuangan pada Dosen FKIP di Universitas Sebelas Maret - Aldisa, Olivia; Indriayu, Mintasih (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to determine 1) the influence of financial literacy on financial management among FKIP lecturers at Sebelas Maret University and 2) the influence of the ease of online shopping on financial management among FKIP lecturers at Sebelas Maret University. The type of research used is quantitative with descriptive methods. The subjects of this research were FKIP lecturers at Sebelas Maret University with a sample of 80 lecturers who were determined using non-practical purposive sampling. Data analysis used in this research used multiple linear regression tests. The results of this research show 1) financial literacy has a positive and significant effect on the financial management of FKIP lecturers at Sebelas Maret University and 2) the ease of online shopping has a positive and significant effect on the financial management of FKIP lecturers at Sebelas Maret University. Apart from that, the results of this research also show that the independent variable has a contribution to the dependent variable. This research can provide an overview of the influence of financial literacy and ease of online shopping on financial management among FKIP lecturers at Sebelas Maret University.